Forensic age estimation in living children: how accurate is the Greulich-Pyle method in Sabah, East Malaysia? - Nang, Khin Mya; Ismail, Abdul Jabbar; Tangaperumal, Anithaa; Wynn, Aye Aye; Thein, Tin Tin; Hayati, Firdaus; Teh, Yong Guang (Frontiers in Pediatrics, 2023)
Background: Gruelich and Pyle’s Radiographic Atlas of Skeletal Development of the Hand and Wrist (GP Atlas) is the most widely used method of determining the bone age (BA) of a child. It is also a widely accepted method for forensic age determination. As there is limited data on bone age for forensic age estimation in local populations, this study aims to assess the accuracy of the GP Atlas for forensic age determination in living Sabahan children. Method: This study recruited 179 children between the ages of 9 years to 18 years. BA estimation of the left-hand anteroposterior radiographs were performed by two radiologists using the Greulich-Pyle method. Results: The BA estimates from two radiologists had strong positive interobserver correlation. In boys, statistically significant overestimation of BA occurs between chronologic age (CA) of 9 and 14 years by as much as 2.1 years. In girls, statistically significant overestimation of BA occurs between CA of 16 and 18 years by as much as 2.1 years. Conclusion: Despite high interobserver agreement of BA assessment, the GP Atlas significantly overestimates the age of the child in younger boys and girls above 15 years old. Our findings suggest that locally validated GP Atlas standards are needed for accurate assessment of BA.